4-BENZOYLPYRIDINE OXIME DERIVATIVE (GIZH-298) VERSUS VALPROIC ACID: THE ANTICONVULSANT POTENTIAL EFFECT IN A MODEL OF EPILEPSY IN RATS WITH COBALT-INDUCED LESIONS - I. O. Gaydukov; S. A. Litvinova; T. A. Voronina; L. N. Nerobkova; L. A. Zhmurenko; G. V. Mokrov; G. G. Avakyan; I. S. Kutepova (Эпилепсия и пароксизмальные состояния)
Objective of the research is to evaluate the anticonvulsant effect of the new original compound GIZH-298 (4-benzoylpyridine oxime derivative) versus valproic acid (VPA) in a model of epilepsy in rats with cobalt-induced lesions.Materials and methods. Modeling of epileptic status was performed using the technique of creating a chronic epileptogenic focus caused by the application of cobalt to the sensorimotor zone of the rat cortex, followed by intraperitoneal administration of homolecysteine thiolactone. Compounds GIZH-298 and VPA were introduced against the background of development of electrographic status with behavioral convulsive seizure manifestations.Results. The study revealed that GIZH-298 at a dose of 60 mg/kg (i. p.) in 50 minutes after injection reduces the number of high-amplitude generalized discharges caused by homocysteine thiolactone in the ipsilateral and contralateral cortex (46-fold decrease), in the hippocampus and hypothalamus (28-fold decrease); eliminates (in 100% of the animals) the generalized tonic-clonic seizures that arise in the advanced stage of status epilepticus. VPA at a dose of 100 mg/kg (i. p.) in 3 hours after injection significantly suppresses the EpA in all evaluated structures with the maximum value in the hypothalamus (28-fold decrease), and after 5 hours in the ipsilateral and contralateral (33-fold decrease). At the same time, VPA eliminates generalized motility of status epilepticus only in 71% of the animals and protects from death 86% of the rats.Conclusion. The compound GIZH-298 significantly earlier (for 2 hours) than the VPA (100 mg/kg) and at a lower dose (60 mg/kg) fully eliminates electrographic (in all evaluated brain structures with the greatest efficiency in the contralateral cortex and the hypothalamus) and behavioral manifestations of unfolded status epilepticus and prevents deaths in 100%.